2022
DOI: 10.3390/jcm11030624
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation (rTMS) as a Promising Treatment for Craving in Stimulant Drugs and Behavioral Addiction: A Meta-Analysis

Abstract: Addiction is a mental disorder with limited available treatment options. The therapeutic potential of repetitive transcranial magnetic stimulation (rTMS) on it, by targeting craving in particular, has been explored with heterogenous results. This meta-analysis uses updated evidence to assess overall rTMS efficacy on craving, differential effects between addiction types clustered into three groups (depressant (alcohol, cannabis, opiate), stimulant (nicotine, cocaine, methamphetamine), and behavioral addiction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 125 publications
1
16
0
Order By: Relevance
“…Our findings are consistent with those of three meta-analyses ( 23 25 ). We included seven DBRCTs in our study, whereas other studies had four ( 25 ), five ( 24 ) and six ( 23 ). Zhang et al included 26 trials, with four ( 20 , 28 , 31 , 32 ) focusing on MUD.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are consistent with those of three meta-analyses ( 23 25 ). We included seven DBRCTs in our study, whereas other studies had four ( 25 ), five ( 24 ) and six ( 23 ). Zhang et al included 26 trials, with four ( 20 , 28 , 31 , 32 ) focusing on MUD.…”
Section: Discussionsupporting
confidence: 93%
“…Our study has several strengths compared with the three other meta-analyses ( 23 25 ). First, we included seven trials, whereas other studies included four, five, and six ( 23 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results may suggest firstly, a recovery of the integrity of prefrontal connections neurites due to active rTMS, and secondly, a close-relationship between the fronto-striatal circuits and the dependency behavior. The main mechanism of action proposed for rTMS in SUD treatment is to activate dopamine function in meso-cortico-limbic system and a reinstaining of extracellular glutamate and dopamine concentrations, which could trigger changes of dendritic spine density, neurotransmitter receptor expression, neuronal degeneration, and microglial activation which could explain the microstructural reversive results in basal ganglia and PFC (8,51,52). A previous study has found that rTMS can reach deep subcortical structures such as the amygdala through stimulation of cortical to subcortical connections (53).…”
Section: Discussionmentioning
confidence: 99%